Pendampingan Produksi Mikroorganisme Lokal (MOL) Bonggol Pisang sebagai Pemberdayaan Peternak di Jorong Tanjung Jati Nagari VII Koto Talago Kabupaten Lima Puluh Kota - Afriani Sandra; Khoirunnisaa’ Khoirunnisaa’; Rahmi Wati; Yolani Utami; Endang Purwati (Warta Pengabdian Andalas, 2021)
The project is carried out in business partner Blue Garden Farm in Tanjung Jati, VII Koto Talago Village, Guguak District, and Regency of Lima Puluh Kota. The location has the potential to develop agriculture and animal husbandry. One of the many agricultural sectors in the region is bananas. People usually only use this fruit while others are wasted. In response to the above problems, a solution to the development and utilization of banana weevil to prepare IMO (Indigenous Microorganisms) was given. IMO is a group of microorganisms derived from natural ingredients that can accelerate the organic composting process. The carbohydrate content of banana weevils is relatively high, 66.2%, which will trigger the development of microorganisms during the fermentation process in the IMO producing process. It aimed to increase the economic value of banana weevil, providing another alternative for farmers to improve agricultural quality. This program used an empowerment method with several approaches, namely learning methods and mentoring with a team in solving problems. An evaluation was carried out to determine the knowledge of farmers' ability about the technology for producing IMO banana weevil. In this community service activity, farmers have made and produced MOL banana weevil. They have been used as a decomposer to manufacture liquid organic fertilizer/bio urine.